DOI: 10.1039/b614705b
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of transition element compounds

Abstract: Scandium, yttrium and the lanthanidesLaser-ablated scandium atoms react with H 2 O/N 2 mixtures to give matrix-trapped (Z 1 -N 2 )Sc(H)OH, (Z 1 -N 2 ) 2 Sc(H)OH and (Z 2 -N 2 )Sc(H)OH. nScH assignments, based on isotopic shifts and DFT calculations, are listed in Table 1. 1 The FTIR spectrum of Sc 3 N@C 80 gave assignments for two isomers-both with trigonal planar Sc 3 N units. 2 There is IR evidence that ScO + in noble gas matrices forms adducts [ScO(Ng) 5Àn (Ng 0 ) n ] + , where n = 0-5, Ng, Ng 0 = Ar, Kr, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 379 publications
(437 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the band in FT-IR studies that corresponds to the stretching vibration of the Fe-N bond (reported for the formation of metal complexes) presents transmittance peaks (region c) of 2160 to 2315 cm −1 (28). Observing the same vibration in β-Hz at 2275 cm and a shoulder at 2310 cm −1 , while Hz is 2318 cm −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the band in FT-IR studies that corresponds to the stretching vibration of the Fe-N bond (reported for the formation of metal complexes) presents transmittance peaks (region c) of 2160 to 2315 cm −1 (28). Observing the same vibration in β-Hz at 2275 cm and a shoulder at 2310 cm −1 , while Hz is 2318 cm −1 .…”
Section: Discussionmentioning
confidence: 99%